When do Companies Train Low Skilled Workers? The Role of Technological Change, Human Resources Practices, and Institutional Arrangements - Philip Wotschack (Proceedings of the Weizenbaum Conference 2019 "Challenges of Digital Inequality - Digital Education, Digital Work, Digital Life", 2019)
The article investigates the role of technological change, HR practices, and institutional organizational differences in training participation of low skilled workers in Germany. By building on institutional theories four hypotheses are derived and tested. Regression analysis based on the IAB Establishment Survey (wave 2011 and 2013) show evidence that the training participation of low skilled workers is shaped by organizational characteristics in terms of advanced production technology, investments in EDP, organizational or technological innovation, institutionalized arrangements and HR policies. While the effects of technology and innovations are of short-term nature, institutionalized arrangements in terms of employee representations and formalized HR practices have an enduring effect: They are positively associated with both a higher likelihood of training investments in low skilled workers and higher rates of continuing training participation among low skilled workers in 2011 and 2013.
Keywords: 330; continuing training; organizations; social inequality; technological change; regulation